Assessing the post-quantitative easing surge in financial flows to developing and emerging market economies - Achille Dargaud Fofack; Ahmet Aker; Husam Rjoub (Journal of Applied Economics, 2020)
The aim of this paper is to assess the surge in financial flows to developing and emerging market economies induced by the Federal Reserve's experience of quantitative easing. Using both panel causality tests and dynamic panel regression models on a data set covering as much as 78 developing and EMEs between 2007Q1 and 2014Q4, it is found on the one hand that QE caused cross-border capital flows in the form of foreign direct investment, an equity portfolios, and bank loans. On the other hand, the study reveals that QE significantly fueled financial flows to developing and EMEs through the portfolio rebalancing, liquidity and confidence channels. In addition, the paper highlights the significant contribution of the fiscal channel and shows that when it comes to post-QE cross-border financial flows, the BRICS exhibit a pattern similar to that of other developing and EMEs.
Keywords: 330; Cross-Border Financial Flows; Developing Countries; Quantitative Easing; Unconventional Monetary Policy